Acquired von Willebrand Syndrome associated to secondary IgM MGUS emerging after Autologous Stem Cell Transplantation for AL Amyloidosis - Victor H Jimenez-Zepeda; Hina Qamar; Adrienne Lee; Karen Valentine; Leslie Skeith (Mediterranean Journal of Hematology and Infectious Diseases)
Acquired von Willebrand syndrome (AVWS) is a rare hemorrhagic disorder that occurs in patients with no prior personal or family history of bleeding. Here, we describe a case of AVWS occurring after autologous stem cell transplantation (ASCT). Interestingly, AVWS developed after bortezomib-based induction and conditioning regimens. Recent evidence suggests that the proximity of the bortezomib therapy to the collection of stem cells with consequent depletion of regulatory T cells after the conditioning regimen could explain some of the unusual autoimmune complications reported in patients receiving bortezomib prior to ASCT. In addition, this patient developed a secondary MGUS post-ASCT, which may have also contributed to the AVWS. To the best of our knowledge, this is the first case of post-ASCT AVWS reported. Prospective data is needed to better elucidate the mechanisms by which these unusual complications occur in patients receiving bortezomib prior to ASCT.